PENGARUH JARAK TRANSDUSER PADA PEMBUATAN BIODIESEL DARI MINYAK JELANTAH BERBANTUKAN ULTRASONIK - Muhammad Ardycha Yudha Ramadhani; Wempi Prayogo; Tiara Priscilla; Nikmah Nurjannah; Faris Achmad Parmadi; Zainal Arifin, (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2024)
Ultrasound-assisted transeserification have been widely used in biodiesel production, since the phenomena of acoustic cavitation has the ability to accelerate the transesterification reactions. This method offers a faster and low energy process compared to conventional. This paper presented the effect of ultrasonic transducer distances on the yield of biodiesel from used cooking oil. The independent variable was the ultrasonic transducer distance (2 cm, 3 cm, 4 cm, 5 cm, and 6 cm). A mixture of 100 mL of used cooking oil with 141,82 mL of methanol and 0,2694 grams of NaOH was put into an erlenmeyer placed in the ultrasonic reactor. Switch on the ultrasonic generator and set the reaction time to 15 minutes. After completion of the reaction process, the mixture was separated in a separating funnel. The biodiesel obtained is then washed and dried. The yield of biodiesel was calculated as the ratio between the weight of biodiesel obtained and the weight of used cooking oil. The results obtained, the optimum transducer distance is 4 cm from the sample with a biodiesel yield of 94,26%.